Pengaruh Manajemen Impresi Pada Perilaku Kewargaan Organisasional: Suatu Studi Empiris - Ariani, D. Wahyu (Universitas Muhammadiyah Yogyakarta, 2014)
In this paper we investigated whether or not impression management effect organizational citizenship behavior (OCB) of employees in service industries in Yogyakarta, Indonesia. The aim of this research also distinguished between impression management and OCB. Based on the previous researchers, I examine that five dimensions of impression management enhance three dimensions of OCB. Three types of OCB and five types of impression management were assessed using modification of previous researchers. A survey was conducted by using questionnaires from previous research. The questionnaires were sent to employees in private service organizations, 171 completed surveys were returned anonymously in sealed envelopes. Validity tests and reliability tests were used to test the questionnaires contents. Independent sample test was used to test difference between impression management and OCB. The correlation between two dimensions and regressions analysis were used to test the relationship among the variables and dimensions. The result proved that impression management is both conceptually and empirically distinct from OCB. Self-promotion, ingratiation, and exemplification dimensions have positive effect on participation dimension, ingratiation, exemplification, and supplication dimensions have positive effect on obedience dimension, and exemplification, intimidation, and supplication dimensions have positive effect on loyalty dimensions. A thorough discussion on the relationship among the variables as well as on self rating is presented in this paper.